An update on hypertensive emergencies and urgencies. Issue 5 (May 2015) - Muiesan, Maria Lorenza; Salvetti, Massimo; Amadoro, Valentina; di Somma, Salvatore; Perlini, Stefano; Semplicini, Andrea; Borghi, Claudio; Volpe, Massimo; Saba, Pier Sergio; Cameli, Matteo; Ciccone, Marco Matteo; Maiello, Maria; et al.
Abstract : Severe acute arterial hypertension is usually defined as 'hypertensive crisis', although 'hypertensive emergencies' or 'hypertensive urgencies', as suggested by the Joint National Committee and the European Society of Hypertension, have completely different diagnostic and therapeutic approaches. The prevalence and demographics of hypertensive emergencies and urgencies have changed over the last four decades, but hypertensive emergencies and urgencies are still associated with significant morbidity and mortality. Different scientific societies have repeatedly produced up-to-date guidelines; however, the treatment of hypertensive emergencies and urgencies is still inappropriate, with potential clinical implications. This review focuses on hypertensive emergencies and urgencies management and treatment, as suggested by recent data.